Upaya Meminimalisir Konflik Perekrutan Badan Adhoc Pemilu 2024 : Studi Kasus Komisi Pemilihan Umum (KPU) Kabupaten Jombang - Amalia, Firda; Winanda, Nieke Rudyanty (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
General elections are a democratic process to directly elect representatives of the people. The process of organizing simultaneous elections will be held again in 2024. The potential for conflict will always accompany every stage of the election implementation. Both internal conflicts and external conflicts. For example, in the General Election Commission (KPU) of Jombang Regency, the conflict that arose was related to the problem of the recruitment system for the 2024 election adhoc body claimed to lack integrity. The purpose of this study is to describe the conflict in the recruitment of adhoc bodies as well as the efforts of the General Election Commission (KPU) of Jombang Regency in minimizing it. The research method uses descriptive qualitative with data collection techniques through document studies and in-depth interviews. The results of the research show that the potential for conflict in the recruitment of adhoc bodies is triggered by public disappointment so that they consider this institution to lack integrity, while efforts to minimize it include providing concrete data transparency.Pemilihan umum merupakan proses demokratis untuk memilih wakil rakyat secara langsung. Penyelenggaraan pemilu serentak kembali dilaksanakan pada tahun 2024. Proses penyelenggaraan pemilu akan selalu beriringan dengan potensi konflik. Baik konflik secara internal maupun konflik secara eksternal. Sebagai contoh di Komisi Pemilihan Umum (KPU) Kabupaten Jombang, konflik yang muncul terkait permasalahan sistem perekrutan badan adhoc pemilu 2024 diklaim tidak berintegritas. Tujuan penelitian ini untuk menggambarkan konflik dalam perekrutan badan adhoc sekaligus upaya Komisi Pemilihan Umum (KPU) Kabupaten Jombang dalam meminimalisirnya. Metode penelitian menggunakan deskriptif kualitatif dengan teknik pengumpulan data melalui studi dokumen dan wawancara yang mendalam. Adapun hasil dari penelitian menunjukkan potensi konflik perekrutan badan adhoc dipicu oleh kekecewaan masyarakat sehingga menganggap lembaga ini tidak berintegritas, sedangkan upaya untuk meminimalisir antara lain dengan memberikan transparansi data yang konkret.